Mitigation of Mild Steel Corrosion in Acid by Green Inhibitors: Yeast, Pepper, Garlic, and Coffee. (2nd December 2012) - Paul, Subir; Kar, Bikash
Abstract : Synthesized organic chemicals, used as inhibitors in mitigating the corrosion of huge quantities of steel articles, pose a major threat to the global environmental problems and health hazards. Naturally occurring products which had been used for natural medication purposes, since the human civilization, are found to inhibit corrosion of steel. Electrochemical studies of the effects of black pepper, garlic, yeast, and coffee on acid corrosion of steel have shown that the corrosion current decreases by manyfold with increase in concentration of the inhibitors. These green inhibitors have been found to get adsorbed maximum up to 70–90%. The polarizing effect is more on cathodic reactions than on anodic reactions, acting as cathodic inhibitor, while a few behaves as anodic to mixed inhibitor. Mechanisms of adsorption are investigated by Frumkin, Temkin, and Langmuir isotherms. The free energy of adsorption is found to be between −15 and −40 kJ/m for most inhibitors, indicating the phenomena of physical adsorption.